CRISPR-Cas9 Mediated Gene Therapy: Current Advancements and Applications Towards Tay-Sachs and Sandhoff Disease - Josefano, Richelle Bertly; Yoel, Abigail; Japri, Beatrice Miranda; Belva, Felicia Lael; Widjojo, Clara Ayu; Hermantara, Rio (Indonesian Journal of Life Sciences, 2024)
Tay-Sachs disease and Sandhoff disease are neurodegenerative diseases that are classified as autosomal recessive lysosomal storage disorders. They are commonly caused by a mutation that occurs in the HEXA and HEXB genes, which are responsible for encoding beta-hexosaminidase-A (Hex A) and beta-hexosaminidase-B (Hex B). Furthermore, Sandhoff's disease symptoms include spinocerebellar ataxia, motor degeneration, sensorimotor neuropathy, tremor, dystonia, and psychosis, which are comparable to Tay-Sachs disease symptoms. The current treatment of Tay-sachs include enzyme replacement therapy, bone marrow transplantation, and administration of genetically modified stem cells with HexA which do not impede neurological dysfunction and were not effective in the long run. On the other hand, there is no standard treatment for Sandhoff but it utilizes bone marrow transplantation which is ineffective. So far, there is only one available gene editing treatment. Therefore, it might be necessary to consider gene editing as a prospective treatment for both diseases, with CRISPR being a primary method. By utilizing Adeno-associated viruses (AAV) as the delivery method for the CRISPR-Cas9 system, it can replace the defective HEXA or HEXB gene with a modified gene termed HEXM, which was found to be the gene codes for the Hex subunit of the same enzyme that is missing in Tay-Sachs and Sandhoff disease. Several challenges of implementing CRISPR-Cas9 technology to treat Tay-Sachs and Sandhoff disease include off-target mutations, unintentional cleavage of the non-targeted sites, and bioethical challenges. Further studies can be explored using various CRISPR-Cas9 systems to improve its efficiency.